MISKONSEPSI MATERI IPA PADA STRUKTUR LAPISAN BUMI DAN KENAMPAKAN ALAM KELAS V SEKOLAH DASAR - Kitaman Hutapea; Idam Ragil Widiyanto Atmojo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to identify the misconceptions of fifth-grade students at SDN Beskalan, Surakarta regarding their understanding of the Earth's layered structure and natural landforms in the science subject. Ideally, each learning activity should provide concrete concepts, as students’ initial preconceptions can influence their understanding of subsequent material. The data collection method used a four-tier test, with the sampling technique employing saturated sampling, meaning all fifth-grade students at SDN Beskalan, Surakarta were included. The collected data were analyzed descriptively using quantitative methods. The results demonstrated that primary-level students misconceptions can be concluded as “moderate” of 55% from a total of 33 students. The most prevalent misconception occurred in the indicator related to identifying the structure of the Earth’s layers and the characteristics of various types of natural landforms, with a misconception rate of 64%, which falls into the high category. The lowest misconception, at 37%, appears in the indicator of identifying the Earth’s outer layers and the atmosphere. This shows that a significant number of primary education students continue to display misconceptions regarding the structure of the Earth’s layers and the characteristics of various natural landforms. The factors causing these misconceptions include incorrect preconceptions, low learning interest, inappropriate reasoning, and the use of scientific terms that lead to students’ misunderstandings. Keywords: misconceptions, science, earth's layered structure and natural landforms, primary-level students